Poly(o-aminophenol) Film Electrodes Synthesis, Transport Properties and Practical Applications - Tucceri, Ricardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This review book is concerned with the synthesis, charge transport properties and practical applications of poly(o-aminophenol) (POAP) film electrodes. It is divided into three parts. The first one has a particular emphasis on problems of synthesis and structure of POAP. The second part deals with the mechanism of charge transfer and charge transport processes occurring in the course of the redox reactions of POAP. The third part describes the promising applications of POAP in the different fields of sensors, electrocatalysis, bioelectrochemistry, corrosion protection, among others. This review covers the literature on POAP in the time period comprised between 1987 and 2013.
From the Contents: Electropolymerization of o-aminophenol on different electrode materials and in different electrolyte media -- Structure of electrochemically synthesized POAP films -- Characterization by IR spectroscopy -- Quartz Crystal Microbalance (QCM) measurements on POAP films electrodes -- POAP film electrodes characterized by their morphology and thickness -- Electrochromic properties of POAP film electrodes.
Keywords: Chemistry; Surfaces (Physics).; Materials Science; Surfaces and Interfaces, Thin Films; Electrochemistry; Characterization and Evaluation of Materials